PENGARUH RASIO KEUANGAN TERHADAP PERUBAHAN LABA PADA BANK BCA DARMO SURABAYA - Karuniawati, Herlina Fitry (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out the influence of financial ratio to the changes of corporate earnings. The research object is carried out at PT BCA Tbk Surabaya Darmo branch which is on Jalan Raya Darmo no. 5 Surabaya. The financial ratio analysis is important for the company in order to show the average influence of independent variable of financial statement in the form of Current Ratio (CR), Return on Asset (ROA), Return on Equity (ROE) and Gross Profit Margin (GPM) to the changes of corporate earnings. The data collection uses secondary data. The data collection is carried out by taking notes or by copying the existing documents in PT BCA Tbk Surabaya Darmo branch. The data analysis technique uses multiple linear regressions analysis with regard to find out the company financial ratio to the changes in earnings.The result of research shows that financial ratio has an influence to the growth corporate earnings. The results of research are: (1) The enhancement of ratio is caused by the reduction of debt at PT BCA Tbk Surabaya Darmo branch in 2010-2012 periods, (2) the companyâs capability in generating cash from activity revenue which has been obtained by the company, so it can be concluded that financial ratio has an influence to the corporate earnings. Keywords:Financial Ratio, Changes in Earnings, Current Ratio (CR), Return on Assets (ROA), Return on Equity (ROE), Gross Profit Margin (GPM)